2016
DOI: 10.1186/s12981-016-0123-x
|View full text |Cite
|
Sign up to set email alerts
|

Re-focusing HIV prevention messages: a qualitative study in rural Uganda

Abstract: BackgroundAfter 30 years, the human immunodeficiency virus (HIV) remains an epidemic of global concern. To support the increasing emphasis on biomedical interventions for prevention requires a renewed and reframed focus on HIV prevention messages to motivate engagement in risk-reduction activities. This paper examines youth and adult perceptions of HIV prevention messages and HIV risk assessment in a generalized HIV epidemic context in Uganda.MethodsWe conducted 24 focus group discussions and 24 in-depth inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…Additionally, in most cases, the ways in which men described testing suggested that it served to validate their continuation of current sexual relationship practices rather than prompting a reconsideration of these practices. This finding is in line with other recent research in Uganda suggesting that while women adhered to public health messages promoting faithfulness as a means of HIV risk reduction, this was not the case with men [ 32 ]. Rather than only sending clients who test negative on their way with a recommendation to retest and use condoms, testing and counseling strategies should support men to reduce risk and build healthier relationships [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, in most cases, the ways in which men described testing suggested that it served to validate their continuation of current sexual relationship practices rather than prompting a reconsideration of these practices. This finding is in line with other recent research in Uganda suggesting that while women adhered to public health messages promoting faithfulness as a means of HIV risk reduction, this was not the case with men [ 32 ]. Rather than only sending clients who test negative on their way with a recommendation to retest and use condoms, testing and counseling strategies should support men to reduce risk and build healthier relationships [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…This “bifurcation” of risk and pleasure in public discourse about sex continues to shape how most young people learn about sex and romance. For instance, one recent study of young Rakai residents’ responses to HIV prevention messaging found that they overwhelmingly perceive sex to be dangerous because of its association with HIV ( Mathur et al, 2016 ). Earmarking funds for abstinence programming also affects the availability of condoms, anti-retroviral therapy, and other SRH technologies, the wholesale costs of which are offset by government subsidies, as well as the willingness of providers to distribute them to young, unmarried men and women, as we discuss below.…”
Section: Introductionmentioning
confidence: 99%